Slenderness limit of FRP-confined rectangular concrete columns. (April 2022) - Saleh, Eman; Tarawneh, Ahmad; Almasabha, Ghassan; Momani, Yazan
Abstract: Providing lateral confinement for RC columns using fiber-reinforced polymers (FRP) wraps or (jackets) improves their compressive strength and ductility. However, many studies found that FRP wraps are less effective in improving the strength and ductility of slender columns compared to short ones and the possibility of column buckling is increased after FRP wrapping. Therefore, for the safe application of FRP jacketing, a slenderness limit that can accurately predict the slenderness threshold that defines short columns should be determined. In this paper, a predictive model to define the slenderness limits of FRP-confined rectangular columns is derived using an accurate design-oriented stress–strain relation of FRP-confined rectangular sections as well as analytically derived loss in column capacity relation. The accurate design-oriented model was obtained by assessing 33 stress–strain models of FRP-confined concrete available in the literature to capture the FRP-confined rectangular columns behavior while the analytically derived loss in column relation was obtained by using this accurate design-oriented model to develop a simplified axial load-bending moment interaction diagram that is subsequently integrated with a curvature-based approach that could capture second-order effects in FRP-columns to come up with a simple analytical expression of the lower slenderness limits for FRP confined rectangular concrete column. The accuracy of the proposed expression was evaluated using a numerical analysis method that was verified with experimental results. The results of the evaluation showed an acceptable accuracy of the derived expression in predicting the slenderness limits for FRP-confined rectangular columns. Moreover, simplified expressions of the derived slenderness limit expression that can be included in design codes are proposed.